Peers and Obesity during Childhood and Adolescence: A Review of the Empirical Research on Peers, Eating, and Physical Activity - Salvy, Sarah-Jeanne (J Obes Weight Loss Ther, 2014)
Obesity during childhood and adolescence is a growing problem in the United States, Canada, and around the world that leads to significant physical, psychological, and social impairment. In recent years, empirical research on factors that contribute to the development and maintenance of obesity has begun to consider peer experiences, such as peer rejection, peer victimization, and friendship. Peer experiences have been theoretically and empirically related to the “Big Two” contributors to the obesity epidemic, eating and physical activity, but there has not been a comprehensive review of the extant empirical literature. In this article, we review and synthesize the emerging theoretical and empirical literatures on peer experiences in relation to: (a) eating (food consumption and food selection); and (b) physical activity, during childhood and adolescence. A number of limitations and issues in the theoretical and empirical literatures are also discussed, along with future research directions. In conclusion, we argue that the involvement of children and adolescents’ peer networks in prevention and intervention efforts may be critical for promoting and maintaining positive behavioral health trajectories.